PWE-318 Emergency admission and short term outcomes in english colorectal cancer patients 1998–2010. (22nd June 2015) - Hicks, G; Morris, E; Burke, D; Finan, P
Abstract : Introduction: English colorectal cancer (CRC) outcomes are inferior to those of similar income level European countries. England has a 'stubbornly high' rate of emergency admission. Identifying where risk of emergency admission is greatest and outcomes of treatment poor, may help target interventions and allow the spread of best practice. Method: Individuals with a first primary diagnosis of colorectal cancer treated between 1998 and 2010 within the English NHS were identified from the National Cancer Data Repository. Numbers of emergency admissions and short term outcomes (mortality at 30- and 90- days) for those undergoing major or minor resection, bypass, stoma or stent were compared. Results: 353, 892 individuals were identified, of which 248, 655 (70.3%) presented electively and 105, 237 (29.7%) presented as an emergency. The proportion of patients presenting as an emergency fell over the study period (32.6% of admissions in 1998, 25.3% in 2010), with emergency patients being more likely to be female, older (≥80years), to have colon cancer, an advanced stage of disease, more co-morbidity and to come from a socioeconomically deprived background. There was wide variation in the numbers of patients admitted as an emergency by hospital trust and in rates of early mortality. Variation in emergency admission rate did not fully account for the significant difference in post-operative mortality between hospital trusts. Conclusion: Comparison of outcomes at a population level allows patterns of disease and trends in its management to be highlighted. It is well known that emergency colorectal cancer patients tend to be older, with more advanced disease, but the finding that emergencies as a proportion of CRC admissions are falling may suggest that recent efforts to reduce emergency admissions (e.g. screening) may be having an impact. The variability in emergency admission rates and rates of early mortality suggests that local factors may heavily influence outcomes, but that high performing trusts may have policies and procedures which could be of benefit to others in the management of the emergency CRC patient. Disclosure of interest: None Declared.